Psychological Study of Hamjan's Characters - Kamran Shahzad, Muhammad; Batool, Shazia; Bibi, Naeema (sourcecoder, 2022)
Man is always a victim of psychological attitudes and mental disorders. In literature, the term psychology was first introduced by Freud for analytical study of this psychological perplexity. Psychology developed in 17th century in Germany and France. This article deals with the beginnings and evolution of psychology, as well as the psychological study of the characters in the novel "Hamjan" by novelist Faris Mughal from Balochistan.